Evaluation Of Antipsicotic Treatment In Skizofrenia Patients At Sambang Lihum Mental Hospital - Muhammad Faqih; Hendera Hendera; Dedi Hartanto (JCPS (Journal of Current Pharmaceutical Sciences), 2021)
Schizophrenia is a very serious mental disorder, which manifests as a collection of symptoms, including impaired thought processes, mood disorders, perceptual disturbances, and behavioral disorders that can lead to disability and dependence. At Sambang Lihum Hospital, South Kalimantan, schizophrenia is always included in the top 10 most treated psychiatric diseases. The purpose of this study was to evaluate the use of antipsychotic drugs in schizophrenic patients and determine its relationship to the length of stay of schizophrenic patients at the Sambang Lihum Hospital, South Kalimantan for the period October – December 2020. This study was an observational study with a cross-sectional design. Data collection was carried out by tracing medical records at the Sambang Lihum Hospital, South Kalimantan for the period October - December 2020. The results of an evaluation study on the use of antipsychotics in people with schizophrenia showed that the right drug was 96.7%, the correct dose was 97.5%, and the frequency was correct. 61.2%. The relationship between rationality and length of stay analyzed using the Chi-square test with the Continuity correction method obtained a significance value of 0.283 (more than 0.05). The conclusion obtained from the use of antipsychotics in schizophrenic patients has not been rational because of the evaluation of accuracy that is not in accordance with the literature. Based on the results of the analysis using the Chi-square test, there is no significant relationship between rationality and length of stay for schizophrenia patients at the Sambang Lihum Regional Mental Hospital, South Kalimantan